HUBUNGAN PSYCHOLOGICAL CAPITAL DENGAN INTENSI BERWIRAUSAHA MAHASISWA STUDI INDEPENDEN PROGRAM AIPBLCIAS (AGILE INNOVATION PROJECT BASED LEARNING – CORPORATE INNOVATION ASIA) ANGKATAN I: RELATION BETWEEN PSYCHOLOGICAL CAPITAL WITH ENTREPRENEURSHIP INTENTION IN INDEPENDENT STUDENTS AIPBLCIAS (AGILE INNOVATION PROJECT BASED LEARNING – CORPORATE INNOVATION ASIA) BATCH I - Rahminingrum Rahminingrum; Nofrans Eka Saputra; Yun Nina Ekawati (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2022)
ABSTRACTIntroduction The unemployment rate is highly, especially at the diploma and university level, where only 12% of the graduates are employed. Therefore, it takes a change in the mindset of students from a job seeker to a job creator, if the entrepreneurial intention of students increases, the number of workers increases. The increase in entrepreneurial intention is influenced by several factors, one of which is psychological capital.This study aims to examine the relationship between psychological capital and the entrepreneurial intention of independent study students of the Agile Innovation Project Based Learning – Corporate Innovation Asia (AIPBL-CIAS) program. Method Quantitative research with correlational research type, the population in this study were students who took part in the independent study program AIPBL-CIAS Batch 1, totaling 250 students. Sampling using random sampling method with a total sample of 131 subjects. The data collection method uses a scale (entrepreneurial intention scale and PCQ scale) which is distributed through google form. Results This study shows a significant positive relationship between Psychological capital and entrepreneurial intentions with R = 0.413 with p value <0.001. The results of the multiple regression test are resilience (r) 0.382 and (p) < 0.001, optimism (r) 0.353 and (p) < 0.001, hope (r) 0.295 and (p) 0.001, self efficacy (r) 0.224 and (p) 0.001. Conclusions Psychological capital provides an effective contribution of 22.4% to entrepreneurial intentions. The variable X that most significantly affects the Y variable is resilience 10.9% and optimism 9.3%. Keywords: Psychological Capital, Entrepreneurial Intention, SIB AIPBL-CIAS ABSTRAK Pendahuluan Tingginya jumlah pengangguran terutama ditingkat lulusan diploma dan universitas yang mana hanya 12% yang bekerja. Oleh karena itu, dibutuhkan perubahan pola pikir mahasiswa dari seorang job seeker menjadi job creator, jika intensi berwirausaha dari mahasiswa meningkat maka dapat meningkatkan jumlah pekerja. Peningkatan intensi berwirausaha ini dipengaruhi oleh beberapa faktor, salah satunya adalah psychological capital. Penelitian ini bertujuan untuk melihat hubungan psychological capital dengan intensi berwirausaha mahasiswa studi independen program Agile Innovation Project Based Learning – Corporate Innovation Asia (AIPBL-CIAS). Metode Penelitian kuantitatif dengan jenis penelitian korelasional, populasi pada penelitian ini adalah mahasiswa-mahasiswi yang mengikuti program studi independen AIPBL-CIAS Angkatan 1, yang berjumlah 250 mahasiswa. Pengambilan sampel menggunakan metode random sampling dengan jumlah sempel 131 subjek. Metode pengumpulan data menggunakan skala (skala intensi berwirausaha dan skala PCQ) yang disebarkan melalui google form. Hasil Penelitian ini menunjukkan adanya hubungan positif yang signifikan antara Psychological capital dengan intensi berwirausaha dengan R= 0,413 dengan p value <0.001. Hasil uji regresi berganda yakni resilliency (r) 0.382 dan (p) < 0.001, optimism (r) 0,353 dan (p) < 0,001, hope (r) 0,295 dan (p) 0,001, self efficacy (r) 0,224 dan (p) 0,001. Kesimpulan Psychological capital memberikan kontribusi efektif sebesar 22,4% terhadap intensi berwirausaha. Variabel X yang paling signifikan mempengaruhi variabel Y adalah resilliency 10,9% dan optimism 9,3%. Kata Kunci: Modal Psikologis, Intensi berwirausaha, SIB AIPBL-CIAS